LMOs/GMOs, the environment and the people: a critical exposition - Ansari, Abdul Haseeb; Jamal, Parveen (2011)
Continuous viable research to develop LMOs/ GMOs by biotechnologists around the world is a sine qua non. It will cater the need of the time in manifest ways, especially by providing subsistence to ever growing populations in developing and least developed countries because they will experience rise of their populations until 2050 which will escalate their food demands. But it is necessarily warranted that all LMOs/GMOs are safe for human consumption and compatible with the environment. On the contrary, they will become counterproductive, i.e. instead of saving lives and enriching the biodiversity of the environment they might bring miseries to the people and erode the biodiversity. This requires restraint on self-interests, economic and personal, on part of developers of LMOs/GMOs, especially biotechnologists, companies engaged with biotechnology researches and governments. As a matter of rule, all LMOs/GMOs must pass through an intensive risk assessment provided in certain international legal instruments before they are allowed to be marketed for human consumption or introducing into the environment. Reproductive cloning is not widely acceptable for manifest reasons, mainly on ethical and religious grounds. So far international trade in LMOs/GMOs is concerned, it the duty of exporting as well as importing countries to perform universally acclaimed lab and field testing in order to ensuring their safety. It is also necessary to have compatibility between the international free trade law and environmental law. In protecting human health, conservation of the biodiversity of the environment and achieving sustainable development, this has to be achieved at any cost. All these are in the public interest. The paper discusses ways and means to achieve the above imperatives in light of relevant international laws and offers certain amicable suggestions for ensuring pubic interests.